Superficial Mycoses In Pregnant Women Consulting At University Hospital Center Of Yaounde - Petmy Lohoue J; Kouam P; Kouam L; Keehia F A (Wolters Kluwer Medknow Publications, 2003)
Pregnant women may contaminate new borns and babies with vaginal candidiasis and ringworms, thus the choice of this group for our study. Cases were recruited at the UHC Yaounde from June 2001 to September 2002. Four hundred and thirty (29.3%) out of 1467 examined presented at least one mycosis. The principal lesions were vaginal thrush 44% and athleteâ€s foot 22%. The causal fungi were essentially yeasts with the predominance of candida albicans (72%) and for the dermatophytes, Trichophyton rubrum (71.84%). The other species were Candida tropicalis, Candida Krusei, Candida parapsilosis, candida glabrata, Malassezia furfur, Trichosporon sp., Trichophyton soundanense, Trichophyton interdigitale, Thrichophyton mentagrophytes and scytalidium dimidiatum. Because these infections affect up to 30% of pregnant women, they should be taken into consideration during prenatal care.